PENGARUH BUDAYA ORGANISASI TERHADAP MANAJEMEN KUALITAS TOTAL PADA PT. DELTA MITRA SEMESTA - Inas Iqbal Daffa’ Ghazy (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2022)
PT. Delta Mitra Semesta from the outside seems like it does not experience any significant problems, but it turns out that there are many problems that occur such as employees lack discipline in work, lack of cooperation and togetherness between employees, lack of company facilities. Complex problems arise due to the consequences of a quality quality in order to survive in the face of globalization and achieve the company's goals. The population and sample in this study are employees of PT. Delta Partners Universe has 120 employees. The study sample of 92 employees and the sampling technique used in this study is roscoe theory (now, 1992) with purposive sampling technique. The data collection technique in this study is primary data by sharing questionnaires with employees of PT Delta Mitra Semesta. Organizational culture has 58.8% while 41.2% is influenced by other variables, Organiation Culture affects simultaneously TQM with a calculated f value of 131.025 and Sig value of 0.000. Organizational culture has a positive influence on TQM with a t calculated value of 11,447 and a Sig value of 0.000. Organizational culture has a positive influence on TQM PT. Delta Partners Universe. Because with the organizational culture in the company will have a positive influence on TQM.